PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI OLEH PERWAKILAN REPUBLIK INDONESIA - Peni Susetyorini (Masalah-Masalah Hukum, 2010)
Sending of Indonesian labour to overseas country that expected can solving the lack of employment problem. It is improve of workers and the family life level and also improve foreign exchange. There are many generated various problem which related to the exploitation practices of Indonesian labour, since recruitment, at working and even until back to Indonesia. The embassy of Republic Indonesia and consulate general of Republic Indonesia are institution that able to be shelter by the Indonesian workers in abroad. Protection effort by the embassy and consular general of Republic Indonesia to Indonesian labour is not optimal yet, this matter caused of some constraint factor, both yuridis and non yuridis resistance. And there are various effort gone trough to overcoming it.